2010
DOI: 10.1016/j.bodyim.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and racial differences in body size perception and satisfaction

Abstract: Body dissatisfaction in women in the United States is common. We explored how women from various racial and ethnic groups used figural stimuli by exploring differences in current and preferred silhouette, and their discrepancy. We surveyed 4,023 women ages 25-45 in an on-line investigation. Participants were identified using a national quota-sampling procedure. Asian women chose a smaller silhouette to represent their current body size, which did not remain significant after adjusting for self-reported BMI. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 23 publications
(38 reference statements)
9
138
0
1
Order By: Relevance
“…For that reason, our results are generalizable to Northern Europe or similar European countries only. We had no additional data on ethnicity, which could have introduced non-differential misclassification and loss of power (25) . Third, the sample yields a high prevalence of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, our results are generalizable to Northern Europe or similar European countries only. We had no additional data on ethnicity, which could have introduced non-differential misclassification and loss of power (25) . Third, the sample yields a high prevalence of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Adults were queried on perception of current, healthy, and ideal body size and dissatisfaction with size using figural stimuli scales matched to BMI; the scale has validity and test-retest reliability for a wide range of subjects. 13,14 Children completed a 19-page standardized face-to-face questionnaire in English, either independently or with aid from research staff, consisting of questions assessing the child's perception of his/her weight status, perception of current, healthy and ideal body size, dissatisfaction with size, perception of mother's size, and what constitutes an underweight, normal-weight, and overweight/obese BMI.…”
Section: Subjectsmentioning
confidence: 99%
“…16,17 National guidelines and normative data link the Stunkard figural stimuli with BMI; the scale has validity and test-retest reliability for a wide range of subjects. 13,14 Adults were asked to specify the child's body size by selecting if the child was "underweight," "normal," or "overweight. "…”
Section: Perceptionmentioning
confidence: 99%
“…Four studies conducted with Native Americans found high levels of BID (Kronenfeld et al, 2010;Rinderknecht & Smith, 2002;Story et al, 1997;Story et al, 1994). Rinderknecht and Smith (2002) incorporated BID, perceptions of healthy body weight, and the prevalence of obesity in a sample of 155 Native American youth.…”
Section: Body Image Dissatisfactionmentioning
confidence: 99%
“…The authors noted that, of the Indigenous Americans studied, approximately half expressed BID and a desire to be thinner. Kronenfeld et al (2010) also assessed BID, though in a much smaller sample of thirty-six adult Native American women. While this sample was small, and was therefore not discussed at length, Kronenfeld et al (2010) reported levels of BID among these women similar to those of European Americans…”
Section: Body Image Dissatisfactionmentioning
confidence: 99%